Multimodal interactive alignment: Language learners’ interaction in CMC tasks through Instagram - Muntaha, Muntaha; Chen, Julian; Dobinson, Toni (University of Hawaii, 2024)
Technological advancement has enabled language learners to employ verbal and nonverbal cues in computer-mediated communication (CMC). These cues can support language use for learners wishing to communicate more effectively in English. Interactive alignment is one phenomenon that shows how humans tend to collaborate in their language use by adapting, priming, and reusing verbal and nonverbal cues to achieve mutual understanding. Informed by a sociocognitive framework, this study explored and documented English language learners’ multimodal interactive alignment during their CMC task engagement through Instagram. We collected data from 30 first-year Indonesian business school learners who participated in seven online CMC tasks using Instagram chat features: text chat, voice chat, and video chat. To examine various interactive alignments (e.g., how interlocutors adapt, prime, and reuse verbal and nonverbal cues to achieve mutual understanding) that occurred during multimodal task communication, we employed multimodal (inter)action analysis. Findings revealed that learners adapted and reused various nonverbal features (e.g., emojis, GIFs, facial expressions, gestures) and verbal cues (e.g., expression, lexical) to convey and comprehend meaning during CMC task completion. Caveats about using various nonverbal alignment patterns for supporting better English online communication were also noted. The study highlights how language learners use the full repertoire of semiotic resources in CMC to maximize their online language learning.